(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this paper is to the q-continuousspace from a quad topological space to a triple topological space,we introduce a conditions to make us able to change the separation axioms and regular space, normal space in q-topologicalspace to the separation axioms and regular space, normal space in tri-topological space and study some of their properties